IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH DUOLINGO APPLICATION AS MEDIA OF LEARNING IN CALL AT ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 TELUKDALAM - Lature, Raihfan Trielman (Universitas Nias Raya, 2025)
The objective of this research aimed to Improving Vocabulary Through Duolingo Application as Media of Learning in CALL at Eleventh Grade Students Of SMA Negeri 1 Telukdalam.This research was conducted by using classroom action research design. The procedure of the research consist into two cycles. The cycle aimed to improve the students’ vocabulary mastery through Duolingo Application in learning. The research findings that showed a significant improvement after the activity was over, in the first cycle there were 13 students’ passed with the percentage 55 % and 23 failed or about 45%. On the post test in the last cycle increase whereby 23 students had been achieve the minimum competence criterion (MCC) with the percentage 80 % and 13 of students failed the test about 20%. Based on the data above the result of this researcher was indicated that there was improved the students vocabulary mastery by using Duolingo Application. The researcher proposes the following suggestion that the Duolingo Application can be applied the media as a strategies because it can enhance the vocabulary comprehence for students’.